CASE REPORT: Interprofessional Collaboration in the Management of Scabies Re-infestation: A Single Case Study in a Rural Area of East Nusa Tenggara Province, Indonesia - Maria Damayanti Gufra Putri Say; Nita Arisanti; Insi Farisa Desy Arya (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2021)
Mr. A presented with complaints of itching and reddish patches on his stomach, palms and fingers for about three weeks. The patient had been diagnosed with scabies infestation three times before and had previously been declared cured.Dermatological exam on this patient showed erythematous papules, rounded, well-defined, discrete spread and multiple measuring 0.2 x 0.2 cm on patient’s hand fingers, palm and abdomen. Excoriation and lichenification were also noticed.The presence of cuniculi were no longer found and some parts had undergone lichenification, marked by darkened skin color due to chronic scratching.The patient is a clove trader who often goes from one village to another to collect cloves. Every time he stops in a village, the patient will stay at a relative's house. He never brings personal towels and gloves while traveling. Often the towels and sarongs that are used by the host are lent to him. He always borrows towels and sarongs from the owner of the house where he is staying. Every time he comes home from traveling, the patient will suffer from itching which causes his wife and children to also get similar itching.